A comparison of car driving, public transport and cycling experiences in three European cities. (September 2017) - Woods, Ruth; Masthoff, Judith
Highlights: Compared experiences of public transport, driving and cycling in 3 European cities. E.g. stress, productivity, health, safety, flexibility, reliability, comfort, speed. Cycling superior/equal to driving and public transport for all aspects bar safety. Cycling evaluated most positively overall. Multiple mode use normal in cities, which may facilitate mode switching away from car driving. Abstract: Private car use in large cities causes congestion and pollution, and should be reduced. Previous research has shown that private cars are preferred over public transport, but it is not known whether that preference holds in large cities that attenuate the usual benefits of car travel. The small body of research comparing cycling with car driving has found a preference for cycling, but it is not clear what that preference is based on, nor its generalizability, particularly beyond those who already cycle frequently. The current study, which was undertaken as part of the EU-funded project, SUPERHUB (SUstainable and PERsuasive Human Users moBility in future cities), compares liking and experiences of car driving, public transport and cycling in three European cities: Barcelona, Helsinki and Milan. Cycling was liked significantly more than car driving and public transport, and was rated significantly more positively than or equivalent to cars on many attributes, including flexibility and reliability, indicating an important role for cycling in the reduction of urban car use. Public transport was rated significantly less positively than car driving for some attributes (e.g. flexibility, reliability) but more positively for others (e.g. value for money, safety), demonstrating that in large cities, the usual advantages of car driving over public transport are considerably attenuated. Almost all these findings were replicated across all three cities, suggesting that they can be generalised. Most city dwellers already use more than one mode regularly, which may support mode change campaigns. In particular, a substantial proportion of car driver commuters already enjoyed cycling on a regular basis, suggesting the potential for mode switching, via multimodality to overcome the obstacle of journey distance.